Role of Plasmapheresis in Renal Transplantation - Abdelbaset Labib, Enas; Ahmed Hashim, Abdelkader; AbdElhamid Elsayed, Abd El Rhman; Ahmed Bichari, Walid (Journal of Neonatal Surgery, 2025)
Focal segmental glomerulosclerosis (FSGS) is a progressive kidney disease that frequently leads to end-stage renal disease (ESRD) and is a major cause of nephrotic syndrome. In patients undergoing renal transplantation, the recurrence of primary FSGS poses a significant challenge, as it can lead to graft dysfunction and loss. The pathogenesis of recurrent FSGS is not completely understood, but it is believed that circulating permeability factors contribute to podocyte injury, leading to glomerular damage and proteinuria. Plasmapheresis, also known as therapeutic plasma exchange (TPE), has emerged as a key strategy for both the prevention and treatment of recurrent FSGS. By removing these circulating factors, plasmapheresis aims to reduce proteinuria and preserve graft function. However, the efficacy of plasmapheresis is highly variable, and many patients require adjunctive therapies to achieve remission. This review explores the pathophysiology of recurrent FSGS, associated risk factors, and the role of plasmapheresis in disease management. Despite its promise, challenges remain, including the need for standardized treatment protocols and better predictors of response. Future research should focus on refining patient selection, optimizing treatment strategies, and exploring novel therapeutic approaches to improve outcomes in renal transplant recipients with recurrent FSGS.